An Empirical Evidences on Cryptocurrencies: Emerging Digital Money in the World - Risal, Nischal (NCC Journal, 2018)
This paper aims toward amplifying the concept of cryptocurrency as emerging digital money in the world and its practices in Nepal. The paper is based on review of various articles, books and relevant websites that provide information regarding cryptocurrencies. The paper highlighted the conceptual part and types of cryptocurrencies in the first section, the major literature review in the context of world in the second section, and the practices of cryptocurrency in Nepal in third section followed by conclusion in final section. An exploratory research design has been adopted in the study. The primary survey has been done to collect the data with self administered questionnaire. The paper reveals the importance of cryptocurrencies in the present context of digital world. The paper concluded that the majority of the respondents are not well known about cryptocurrency in Nepal. The respondents are found interested to invest with knowledge, policy and security on cryptocurrency in Nepal. This thematic based research paper will create a platform for the researcher to study the practical scenario of cryptocurrency. NCC Journal Vol. 3, No. 1, 2018, page: 100-107